PENGARUH TEKNOLOGI INFORMASI TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI MANAJEMEN YANG BERDAMPAK TERHADAP KINERJA MANAJERIAL - Helmi Yuliantini Gandari (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2018)
The purpose of this study is to determine the influence of information technology to the quality of management accounting information system and know the influence of quality management accounting information system to managerial performance in PT Graha Pangan Lestari. This research uses data analysis method using Partial Least Square (PLS). The results of this study indicate that information technology has a significant effect on the quality of management accounting information system of 72.5% and the quality of management accounting information system significantly influence the managerial performance of 71.1%.